Analisis Metode Dakwah Husain Basyaiban di Media Sosial - Efendi, Erwan; Putri Irawan, Ravika; Pasaribu, Nurhasanah; Al Hafiz, Syafruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Da'wah is an activity of inviting and influencing people towards the straight path wisely in accordance with God's commands. This is done for every individual and community to want to improve themselves by doing good deeds and deepening the teachings of the Islamic religion. Da'wah must be carried out by people who are intelligent, civilized and have noble character. Da'wah media continues to evolve by following technology which is becoming more advanced day by day, one of the media used for preaching is social media. You Tube, Instagram, and Tik Tok are examples of social media that are currently widely used by preachers to preach. Husain Basyaiban is one of the young preachers who uses social media as a medium for his preaching. The preaching delivered by Husain had an influence on readers and viewers, because it was packaged well using simple language and strong arguments so that it was easy for his followers to understand. Therefore, researchers are interested in analyzing the preaching methods used by Husain. This research focuses on the da'wah methods and social media used by Husain Basyaiban. This research was carried out using a qualitative approach using the netnographic method where primary sources were obtained from posts and videos uploaded by Husain Basyaiban and secondary data sources were obtained from previous journals and articles. With data collection techniques by means of online documentation and observation. From the results of this research, it was found that Husain used da'wah methods which were categorized into three methods, namely the Al-Hikmah, Mauidzotul Hasanah, and Mujjadi methods. Then there is the development of Husain's social media at this time, with the username kadamsidik for 168 thousand subscribers on You Tube, the username basyasman for 1.9 million followers on Instagram, as well as the username @kadamsidik00 for 6 million followers and also 327.1 million likes on all videos which was uploaded from the beginning of 2020 until now on September 24 2023 on Tik Tok. Researchers hope that this research can be studied and researched more deeply by other researchers, both with other methods and objects.